On phylogenetic relationships among major lineages of the Gammaherpesvirinae - McGeoch, Duncan J.; Gatherer, Derek; Dolan, Aidan (Journal of General Virology, 2005)
Phylogenetic relationships within the subfamily Gammaherpesvirinae of the family Herpesviridae were investigated for three species in the genus Lymphocryptovirus (or γ1 group) and nine in the genus Rhadinovirus (or γ2 group). Alignments of amino acid sequences from up to 28 genes were used to derive trees by maximum-likelihood and Bayesian Monte Carlo Markov chain methods. Two problem areas were identified involving an unresolvable multifurcation for a clade within the γ2 group, and a high divergence for Murid herpesvirus 4 (MHV4). A robust final tree was obtained, which was valid for genes from across the virus genomes and was rooted by reference to previous analyses of the whole family Herpesviridae. This tree comprised four major lineages: the γ1 group of primate viruses; a clade of artiodactyl γ2 viruses; a clade of perissodactyl γ2 viruses; and a clade of γ2 viruses with a multifurcation at its base and containing Old World and New World primate viruses, Bovine herpesvirus 4 and MHV4. Developing previous work it was proposed, on the basis of similarities between the gammaherpesvirus tree and the tree of corresponding mammalian hosts, that the first three of these major viral lineages arose in a coevolutionary manner with host lineages, while the fourth had its origin in an ancient interspecies transfer. Transfer of dates from mammalian palaeontology then allowed estimation of dates for nodes in the gammaherpesvirus tree.